The association between breastfeeding and childhood obesity/underweight: a population-based birth cohort study with repeated measured data - Weiqin Li; Jiarong Yuan; Leishen Wang; Yijuan Qiao; Enqing Liu; Shuo Wang; Junhong Leng (BMC, 2022)
Abstract Background The impact of breastfeeding on childhood obesity has long been under debate, with most research showing significant association, and others showing weak or no association between breastfeeding and childhood obesity. What's more, almost all of the previous studies focused on the association between breastfeeding and childhood obesity, and no studies have assessed the association between breastfeeding and childhood underweight. This study aimed to examine the association between breastfeeding and childhood obesity as well as childhood underweight from 1 to 6 years old. Methods A retrospective population-based cohort study of 59,564 children born between May 2009 and April 2013 in China was conducted using the healthcare records data from the Tianjin Maternal and Child Healthcare System. Information on infant breastfeeding (exclusive breastfeeding, mixed feeding, and exclusive formula feeding) within 6 months old and childhood growth (6 times of repeated measured weight and height from 1 to 6 years old) was collected. Multinomial logistic regression was used to test the potential associations between infant feeding modalities and childhood growth (underweight, normal weight and obesity). Results Compared with exclusive formula feeding, breastfeeding was inversely associatied with childhood obesity from 2 to 6 years old, and there was a trend from mixed feeding to exclusive breastfeeding (P trend < 0.05). The largest association with obesity was displayed at 3 years old, with the multivariable adjusted odds ratios (ORs) for exclusive formula feeding, mixed feeding and exclusive breastfeeding of 1.00, 0.62 (95% CI 0.49, 0.80) and 0.57 (95% CI 0.44, 0.74) (P trend = 0.001), respectively. Compared with exclusive breastfeeding, exclusive formula feeding may increase the risk of childhood underweight at 3 and 5 years old. Conclusions Breastfeeding was inversely associated with the risk of childhood obesity from 2 to 6 years old, and there was a trend from mixed feeding to exclusive breastfeeding. Infant exclusive formula feeding might be a risk factor for childhood underweight at preschool time.